2014
DOI: 10.5194/acp-14-3751-2014
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol's optical and physical characteristics and direct radiative forcing during a shamal dust storm, a case study

Abstract: Abstract. Dust aerosols are analyzed for their optical and physical properties during an episode of a dust storm that blew over Kuwait on 26 March 2003 when the military Operation Iraqi Freedom was in full swing. The intensity of the dust storm was such that it left a thick suspension of dust throughout the following day, 27 March. The synoptic sequence leading to the dust storm and the associated wind fields are discussed. Ground-based measurements of aerosol optical thickness reached 3.617 and 4.17 on 26 and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 96 publications
3
34
0
Order By: Relevance
“…Different parts of the Middle East, especially the United Arab Emirates (UAE) are affected by dust storms (horizontal visibility lies between 0 and 1 km) for almost 30% of the time during various seasons. The frequency of occurrence of dust storms peaks during the premonsoon season (March-May) when dust aerosols are transported by southwesterly winds from the arid and semi-arid regions around the Arabian Peninsula (Ackerman & Cox, 1982;Middleton, 1986;Aher, Pawar, Gupta, & Devara, 2014;Prakash, Stenchikov, Kalenderski, Osipov, & Bangalath, 2015;Saeed, Al-Dashti, & Spyron, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Different parts of the Middle East, especially the United Arab Emirates (UAE) are affected by dust storms (horizontal visibility lies between 0 and 1 km) for almost 30% of the time during various seasons. The frequency of occurrence of dust storms peaks during the premonsoon season (March-May) when dust aerosols are transported by southwesterly winds from the arid and semi-arid regions around the Arabian Peninsula (Ackerman & Cox, 1982;Middleton, 1986;Aher, Pawar, Gupta, & Devara, 2014;Prakash, Stenchikov, Kalenderski, Osipov, & Bangalath, 2015;Saeed, Al-Dashti, & Spyron, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above, we are led to suggest that environmental changes in desert morphology, possibly related to 'Operation Iraqi Freedom' in 2003, may have lead to the observed increase in DU in 2003. Furthermore, a case study by Saeed et al (2014) during 'Operation Iraqi Freedom' suggested an increase in dust storm intensity in the N Gulf as a result of military activity. 40°N 36°N 32°N 28°N 24°N 20°N 30°E 36°E 42°E 48°E 54°E 30°E 36°E 42°E 48°E 54°E 30°E 36°E 42°E 48°E …”
Section: Climate Variability In the Nmentioning
confidence: 99%
“…So far, the aerosol research has been focused on aerosol optical properties (Elminir, 2005;El-Metwally and Alfaro 2013), airborne dust (monitoring, source region, and transport) (Satheesh et al, 2006;El-Askary and Kafatos, 2008;Reid et al, 2008;El-Askary et al, 2009;Dada et al, 2013;Alam et al, 2014;Gherboudj and Ghedira, 2014;Saeed et al, 2014;Basha et al, 2015), transport of anthropogenic aerosols (e.g., Kuwait: impacts of 1991 oil fire plumes in Kuwait) (Lowenthal et al, 1992;Daum et al, 1993;Herring et al, 1996;Rudich 2003;Tazaki et al, 2004;Bonazza et al, 2007), chemical analysis and gaseous pollution (Shaka' and Saliba, 2004;Kouyoumdjian and Saliba, 2006;Saliba et al, 2007;Mahmoud et al, 2008;El-Araby et al, 2011;Dobrzhinsky et al, 2012;Boman et al, 2013;Daher et al, 2013;Engelbrecht and Jayanty, 2013;Hassan et al, 2013;Waked et al, 2013a, b;Jafar et al, 2014;Roumie et al, 2015), and particulate matter (PM) (Saliba et al, 2010;Khodeir et al, 2012;Habeebullah, 2013;Munir et al, 2013a, b;Rushdi et al, 2013;Shaltout et al, 2013;Alghamdi et al, 2014a, b;Hussein et al, 2014a;…”
Section: Introductionmentioning
confidence: 99%